The impact of individualization of land use on productivity and structural transformation of the Russian agricultural sector ("Journal "U". Economy. Management. Finance.", 2025)
The article is devoted to the analysis of transformation processes in the agricultural sector of Russia, with a focus on the relationship between the individualization of land use and the dynamics of agricultural production. Based on statistical data and a comparative analysis with the CIS countries, the hypothesis is investigated that the growth of the share of land in individual use positively correlates with an increase in gross agricultural output and the profitability of rural households. The research methodology includes a regression analysis of panel data for 80 regions of Russia for the period since 1998, as well as a qualitative analysis of institutional changes. The results indicate the need for further reform of land relations and the development of market mechanisms to achieve a balanced size structure of farms.
Keywords: agricultural sector of Russia; land reform; individualization of land use; agricultural productivity; private subsidiary farms; structural changes; land markets